Robotic Pieloplasty: a case report - Jasėnas, Marius; Venckus, Raimundas (Lietuvos chirurgija, 2019)
[full article and abstract in Lithuanian; abstract in English]Minimally invasive surgeries for better operative and postoperative results are increasingly being performed by urologists in urology. Robotic pyeloplasty one of the methods that facilitate the joining of the pyramidal segment, shortens the surgery length, is less tiring to the doctor, who performs a surgery, also, shortens the hospitalization time.The first robotic (Senhance Transenterix system) pyeloplasty surgery to a 61 years old patient with severe underlying diseases was performed on 04 01 2019 in Klaipėda university hospital. The operative and post-operative periods passed without complications, and the patient was discharged from hospital on the fourth day. After 2 months, the patient has no clinical complaints, the CT scan revealed regressing hydronephrosis after the robotic kyphoplasty surgery.After evaluating the obtained results, it can be stated that robotic kyphoplasty surgery is a minimally invasive, safe and effective surgical method with a very fast patient rehabilitation.
Keywords: pieloplasty; minimaly invasive sugery; robotic surgery